Investigation of strengthening effect on the machining rigidity in longitudinal torsional ultrasonic milling of thin-plate structures. (February 2020) - Wu, Chenjun; Chen, Shijin; Cheng, Kai; Xiao, Caiwei
Weak-stiffness structures are difficult to be machined because of their low stiffness, large deformation and poor stability through conventional machining. Ultrasonic-assisted machining has the superiority of reducing cutting force and increasing stiffness, which can result in better cutting performance particularly in machining weak-stiffness structures. In this article, the stiffness-strengthening effect of longitudinal torsional ultrasonic milling of thin-plate structures is thoroughly investigated by theoretical analysis and experimental trials. The strengthening coefficient of equivalent stiffness is obtained by analyzing the forced vibrations of the thin-plate structure under conventional milling and ultrasonic milling loading, respectively. The ultrasonic vibration period and the actual cutting time in one ultrasonic vibration period are proved to be the factors responsible for the stiffness-strengthening effect in ultrasonic cutting. When compared with conventional milling, longitudinal torsional ultrasonic milling trials show that the equivalent stiffness of the machining system can be increased by 1.92 times, despite the rigidity strengthening coefficient decreases with the increasing spindle speed.